SOSIALISASI PENANGGULANGAN BAHAYA KEBAKARAN DI ATAS KAPAL BAGI MASYARAKAT NELAYAN DAN ANAK BUAH KAPAL DI DESA PASIR, KABUPATEN KEBUMEN, JAWA TENGAH - Juharis; Eka Setia Budi; Ahmad Adiarsa, Hilda Emeraldo; Pratama, Ardian; Sithaningtyas; Fatimah; Putri, Indira Ari; Djari, Janny Adriani (Politeknik Ilmu Pelayaran Semarang, 2024)
Socialization of fire hazard management on boats for the community fishermen and crew members was held in Pasir Village, Ayah Subdistrict, Kebumen Regency. Kebumen Regency. This socialization activity was held to provide education to fishermen and crew members on the coast of Pasir village, about how to deal with fire hazards while on the ship.